Bioprospecting of microalgae from sewage water for production of lipids and lactic acid - Halder, Nirmalya (My University, 2025)
In today's world, there is a growing need for sustainable solutions to address environmental pollution and resource depletion. Microalgae play a dual role in environmental cleanup and resource generation, highlighting the importance of integrating biological methods into wastewater treatment protocols. Native microalgae exhibit exceptional resilience and efficiency in nutrient sequestration, effectively removing nitrates and phosphates that contribute to water pollution and eutrophication. These microalgae hold great potential in the biorefinery industry due to their high lipid, protein, and carbohydrate content, which can be converted into valuable biofuels and bioproducts such as biodiesel, bioethanol, and lactic acid. This approach offers an eco-friendly alternative to traditional methods and provides a pathway for sustainable bioproduct synthesis, contributing to the circular economy and reducing dependency on fossil fuels. In this study, native microalgae were isolated from secondary sewage water effluent. These isolates were screened for their high seasonal presence and lipid content, along with protein and carbohydrates. They were cultivated in sewage water to facilitate nutrient sequestration, and the growth dynamics impact of CO2 sparging for high biomass production was studied. The lipid-extracted algal biomass (LEAB) from the selected microalgae was pretreated to obtain algal hydrolysate, which was subsequently used for lactic acid fermentation. Microalgal species isolated from a sewage treatment plant were identified through 18S rRNA sequencing and evaluated for their biochemical composition to assess their potential for biorefinery applications. Unicellular microalgae, including Chlorella sp., Dictyosphaerium sp., Graesiella sp., and Scenedesmus sp., Desmodesmus sp., Tetranephris sp., and Coelastrella sp., were characterised. Biochemical analysis revealed total lipid contents ranging from 17.49 ± 1.41% to 47.35 ± 0.61% w/w, carbohydrate contents from 12.82 ± 0.19% to 64.29 ± 0.63% w/w, and protein contents from 8.55 ± 0.19% to 16.65 ± 0.20% w/w. Fatty acid methyl ester (FAME) analysis indicated the presence of fatty acids such as hexadecane (C16:0) and eicosane (C20:0), making specific isolates, including Chlorella sp., Coelastrella sp., and Scenedesmus sp., suitable for biodiesel production. The high protein content in Scenedesmus sp. and Chlorella sp. highlights their potential as food or feed supplements, while the high carbohydrate content in Dictyosphaerium sp., Coelastrella sp., and Scenedesmus sp. suggests their suitability for fermentative production of alcohol and organic acids. Seasonal resilience viii and dominance of Chlorella sp. and Scenedesmus sp. support their scalability for sewage-water cultivation and biomass utilisation in biorefineries. Growth kinetics and nutrient removal efficiency of microalgal isolates were further studied in synthetic (BG-11) and wastewater media, including raw and autoclaved secondary wastewater effluent (RSWE and ASWE). The effect of intermittent CO2 sparging was assessed to optimise biomass productivity and nutrient assimilation. Among the isolates, Scenedesmus sp. DGNH-4 exhibited the highest biomass productivity, achieving 38.67 ± 1.01 mg L-1 d-1 in BG-11 and comparable rates in wastewater media under CO2 sparging. Specific growth rates improved with sparging, reducing doubling times, while nutrient removal efficiencies were also enhanced, with nitrate removal of 63.49 ± 1.99 mg L-1d-1 and phosphate removal of 2.13 ± 0.02 mg L-1d-1 in RSWE. These findings emphasise the potential of Scenedesmus sp. DGNH-4 for scalable wastewater treatment, nutrient recovery, and bioresource applications while highlighting the role of CO2 sparging in enhancing cultivation efficiency. Finally, a biorefining process was developed to utilise the lipid-extracted algal biomass (LEAB) of Scenedesmus sp. for lactic acid production. Hydrolysis of LEAB carbohydrates into fermentable sugars was optimised using 0.9 M H2SO4 at 121°C for 5 minutes, resulting in a reducing sugar concentration of 7.41 ± 0.56 g L-1 and a saccharification yield of 37.03 ± 2.81%, with minimal inhibitor generation. The hydrolysate, neutralised with calcium hydroxide and supplemented with peptone, supported fermentation by Lactobacillus casei, achieving lactic acid production of 1.2 g L-1 with 78.53 ± 1.21% sugar conversion and a yield of 0.81 ± 0.0042 g/g. This demonstrates the high potential of LEAB as a sustainable feedstock for lactic acid production, supporting the development of efficient and integrated microalgal biorefineries.
Keywords: lactic acid; microalgae; waste water; bioprospecting; lipid extracted algal biomass; biofuels; microalgal diversity